Soluble CD163 correlates with lipid metabolic adaptations in type 1 diabetes patients during ketoacidosis - Svart, Mads (J Diabetes Investig, 2018)
INTRODUCTION: Diabetic ketoacidosis (DKA) is associated with inflammation and increased lipolysis. The macrophage activation marker, soluble CD163 (sCD163), is associated with obesity, non‐alcoholic fatty liver disease and type 2 diabetes. We aimed to investigate whether sCD163 correlates with key elements of lipolysis in type 1 diabetes patients during mild DKA. MATERIALS AND METHODS: We investigated nine patients with type 1 diabetes twice during: (i) euglycemic control conditions and a bolus of saline; and (ii) hyperglycemic ketotic conditions induced by lipopolysaccharide administration combined with insulin deprivation. Blood samples, indirect calorimetry, palmitate tracer and adipose tissue biopsies were used to investigate lipid metabolism. RESULTS: We observed a significant increase in plasma sCD163 levels after lipopolysaccharide exposure (P < 0.001). Concentrations of sCD163 were positively correlated with plasma concentrations of free fatty acids, palmitate rate of appearance and lipid oxidation rates, and negatively correlated to the expression of G0/G1 switch 2 gene messenger ribonucleic acid content in adipose tissue (P < 0.01 for all). Furthermore, sCD163 levels correlated positively with plasma peak concentrations of cortisol, glucagon, tumor necrosis factor‐α, interleukin‐6 and interleukin‐10 (P < 0.01 for all). Data on lipolysis and inflammation have previously been published. CONCLUSIONS: Macrophage activation assessed by sCD163 might play an important role in DKA, as it correlates strongly with important components of lipid metabolism including free fatty acids, palmitate, lipid oxidation, G0/G1 switch 2 gene and pro‐inflammatory cytokines during initial steps of DKA. These results are novel and add important knowledge to the field of DKA.